Systematic review of community efforts in early handling post-exposure prophylaxis cases of rabies animal bite transmission - Tanti Marjiana; Asti Melani Astari; Lilik Zuhriyah (Intelektual Pustaka Media Utama, 2021)
Rabies is acute progressive encephalitis, caused by a virus that enters the body after the bite of an infected animal, and migrates to the brain. Management of rabies animal bite transmission (GHPR) with post-exposure prophylaxis (PEP) is the most important strategy for preventing rabies-related mortality. GHPR victims need the right PEP. Effective post-exposure provision depends on good individual awareness about rabies and access to health services. To find out the efforts made by the community in raising public awareness to get PEP by doing initial handling after GHPR appropriately. This systematic review begins by identifying the literature on scientific articles that have been published in 2014-2019 in international databases namely Proquest, ScienceDirect, Springer and Ebsco. Selection is done by systematic reviews and meta-analyses (PRISMA) flow diagram and selected using the Joanna Briggs Institute (JBI) checklist format tools. The nine relevant articles were obtained to be analyzed into a systematic review, namely four articles from the Proquest database, two articles from the ScienceDirect database and three articles from the Ebsco database. Community efforts in initial treatment of victims exposed to GHPR are immediately carried out by applying wound washing, providing antiseptics and immediately to health care facilities to get further treatment. The community should understand important information about handling practices in GHPR wound management appropriately. PEP was an immediate action for early relief when victims are exposed to GHPR. PEP was conducted as an effort to prevent the virus from developing into dangerous stages that could result in death